Phytochemical screening and antibacterial activity of piper sarmentosum stems / Norhidayah Sahariman - Sahariman, Norhidayah (Faculty of Applied Sciences, 2017)
The objectives of this study are to extract P. sarmentosum stems using soxhlet extraction technique, to perform the chemical and biological activities of P. sarmentosum stems, to determine the TLC profiling of the extracts sample by using thin layer chromatography method with variety of solvent system and to screen the antibacterial activity of plant crude extract using disc diffusion method. Ground P. sarmentosum stems were extracted using soxhlet extraction and using two different type of solvent which are chloroform and ethanol. Then each extract was evaporated using rotary evaporator to produce crude. The phytochemical screening has been performed. During phytochemical screening, phenol and alkaloid has been detected in chloroform extract meanwhile in terpenoid, saponin, flavonoid and tannins have been detected in ethanol extract. TLC profiling of the extracted sample was done using thin layer chromatography method with variety of solvent system. Antibacterial activity was tested between the P. sarmentosum extract against two types of Gram-positive(+) bacteria which were S. aureus andB. subtilis and another two type of Gram-negative (-) bacteria which were S. typhymirium and E. coli by using disc diffusion method. In antibacterial activity, ethanol extract showed the highest inhibition zone against E. coli with 11.50 mm meanwhile, chloroform extract showed the highest inhibition zone against E. coli with 9.00 mm as compared to other bacteria.